Looking through two lenses: reflections on transnational and translocal dimensions in Marseille-based popular music relating to the Comoros. Issue 5 (3rd September 2018) - Englert, Birgit
ABSTRACT: This article starts from the observation that whenever new concepts become popular, they are applied to more and more contexts until they have become so inclusive that they risk losing their analytical power. This tendency also shapes the relationship between the concepts of transnationality and translocality, which is discussed here with a focus on popular music. More precisely, this article draws on research on two musical actors who are both based in the French city of Marseilles and who both relate to the Indian Ocean archipelago of Comoros: the internationally acclaimed rapper Soprano and the group Afropa, who play Afrofolk on the margins of the music scene in Marseilles. Besides the different levels of success they experience and the distinct musical genres they embody, these musicians represent different generations of a Franco-Comorian 'diaspora'. Their musical oeuvre, motivations and ambitions, as well as the perception of their music by different audiences, will be discussed with respect to the notions of transnationalism and translocality that become apparent.